Capital-skill complementarity and inequality: a sensitivity analysis - Linnea Polgreen; Pedro Silos (Federal Reserve Bank of Atlanta, 2005)
In "Capital-Skill Complementarity and Inequality: A Macroeconomic Analysis," Krusell et al. (2000) analyzed the capital-skill complementarity hypothesis as an explanation for the behavior of the U.S. skill premium. This paper shows that their model's fit and the values of the estimated parameters are very sensitive to the data used: Alternative measures of the capital series predict skill premia that bear little resemblance to the data. We also include ten additional years of data to address the claim made by other authors that the evolution of the skill premium changed during the 1990s, but we find little evidence of this change.
Keywords: 330; Bildungsertrag; Fachkräfte; Ungelernte Arbeitskräfte; Relativer Preis; Arbeitsangebot; Technischer Fortschritt; Kapital; Produktionsfunktion; Theorie; USA